A Semiotic Analysis of Nationalism in Bakatsir's 'Biladaka Ya Hatta' through Riffaterre's Theory - Fikri, Maulana Muhammad; Fitriani, Laily; Hasaniyah, Nur; Ayvaz, Harun (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This study analyzes Ali Ahmad Bakatsir’s Biladaka Ya Hatta using Michael Riffaterre’s semiotic theory to explore themes of nationalism during Indonesia’s independence struggle. The poem, rich in metaphor, enjambment, and symbolic language, portrays both the spiritual and political dimensions of Indonesia’s fight for freedom. Through Riffaterre’s heuristic and hermeneutic reading methods, the research uncovers how the poem's surface meanings evolve into deeper interpretations. Bakatsir’s strategic use of language highlight’s themes of patriotism and unity, with vivid imagery such as